Stress, Anxiety, And Depression Among Dentists Three Years into The Pandemic - Werfalli , Sumeia; Gehani, Ghada; Taher, Sanosi (Libyan Journal of Public Health Practices, 2024)
The COVID-19 pandemic had a significant impact on healthcare workers globally, including the psychological wellbeing of dentists. To evaluate the effect of the early phase of the pandemic on the long-term psychological well-being of dentists, this study assessed dentists’ mental health outcomes at two time points, at fall 2020 (six months into the pandemic), and at winter 2023 (three years into the pandemic). Specifically measuring the prevalence of symptoms of depression, anxiety, stress, and potential associated risk factors. The study surveyed dentists in Libya who responded to the study questionnaire Specifically measuring the prevalence of symptoms of depression, anxiety, stress, and potential associated risk factors. The study surveyed dentists in Libya who responded the study questionnaire in fall 2020 (n = 67) and winter 2023 (n = 38). The survey included self-report measures assessing four mental health outcomes: depression, anxiety, and stress. The chi-square test was used to compare mental health outcome measures between fall and winter. The prevalence of self-reported depression, anxiety, and stress decreased between fall 2020 and winter 2023 (40% vs. 37%, p =0.27; 55% vs. 42%, p = 0.37; 97% vs. 71%, p = 0.11 respectively). These estimates were particularly higher among those with a history of psychiatric disorder. Three years into the coronavirus disease 2019 pandemic, poor mental health outcomes were highly prevalent among dentists. Further research is needed to assess contributing factors in this specific population. Dental syndicates should promote targeted programs and services aimed at improving dentists’ well-being.